ROLE OF MEDIA BEHAVIOR IN DISSEMINATION OF ADVERTISING MASSAGE TROUGH TRADITIONAL ADVERTISEMENT (International Journal of Food and Nutritional Sciences, 2022)
The role of mass media notice in federal class actions explores how media planning theories, concepts, and methods might inform the jurisprudence of class action notice and aid in more informed judicial consideration of advertisement notice plans. The number of alternative to traditional advertisement is continuously rising. The trend towards sales promotion, direct response marketing and public relations continues, as a growing number of business shift resources away from traditional advertising. Advertising message involvement has long been a topic of interest in the advertising literature. Despite the many benefits of the effects on consumer’s responses to advertising which has not been shown as numerous significance. This study investigates the theoretical and methodological issues regarding predisposition factors and the impact they have on experimenter-generated manipulations of advertising message involvements.